A study on sexual harassment in hospitality industry of Malaysia / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Wan Mohammad, Siti Hajar; Md Sabri, Sabiroh; Jislan, Fatanah; Mohd Said, Nur Shafini (2013)
The problem of sexual harassment in workplaces is known as a serious issue and can be considered as an occupational hazard and a violation of human rights. Although most of the studies on sexual harassment have been conducted in the west, such behaviour has been acknowledged by many sectors in Malaysian many years back. Many researches reveal that hospitality industry particularly is more likely than other industries to have problems with sexual harassment due to the nature of the jobs in the hotel. Indeed, the hospitality industry may be possible to experience sexual harassment because of its characteristics, such as long and unusual working hours, the interaction of persons in the delivery of service and the need to satisfying guests’. This study is conducted to gain an understanding of the issue of sexual harassment in the hospitality industry in Malaysia. Specifically, the objectives of this study are to examine the types of sexual harassment experienced by employees in the hospitality industry, to determine the effect of sexual harassment to the victims and to identify the risk factors that contribute to the act. A modified self-administered questionnaires designed by the DEOC Task Force on Discrimination and Sexual Harassment, USA was used as the main data collection instrument in this study. A total of 260 questionnaires were distributed to male and female employees working in various hotels and resorts in Terengganu. The respondents were selected using quota sampling technique. Data was analyzed using descriptive statistics such as mean, frequency and percentage.